Kelangsungan hidup larva ikan Betok (Anabas testudineus) dengan pemberian pakan alami dan pakan buatan - Nyata Susila (JURNAL ILMU HEWANI TROPIKA (JOURNAL OF TROPICAL ANIMAL SCIENCE), 2017)
This research aims to know the survival rate of Climbing Perch (Anabas testudineus) larvae fed with live and artificial feed. This study used a Randomized Complete Design with three treatments and three replicates. The treatments were feeding of egg yolks (A), feeding of live feed/plankton (B) and feeding of the factory feed (C). The survival rate of Climbing Perch larvae obtained from the highest treatment B (37.33%), followed by treatment A (23.66%) and treatment C (0.00%). Key words : Anabas testudineus, larvae, live feed, survival rate.